Power-knowledge Relations of The Elder and The Younger Madurese Muslim Scholars in Propagating Islamism in Madura: A Counter-narrative - Abd A'la; Ahwan Mukarrom (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
This article examines the relationship between religion-politics and knowledge developed by the Kiai Tua and Kiai Muda in Madura. The Aliansi Ulama Madura (AUMA), or The Alliance of Madurese Ulema representing the Kiai Tua, and the Forum Kiai Muda (FKM) or The Forum of Young Ulema for Kiai Muda have actively propagated the idea of Islamism in Madura. By employing Foucault’s theory of power relations, this article discovered that the relation of power and knowledge might put Madura at risk. This theory, which was constructed by the AUMA, FKM, and their organizational networks, may likely cause intolerant and exclusive views. Their religious understanding and publicity have a militant and robust desire to make their ideological narratives, mainly of Islamic revival, along with the aspiration to establish a global Islamic leadership system, come into existence. This resistant attitude subsequently makes the ideology grow into an extreme, radical, and intolerant movement. For this reason, several moderate groups, such as Pengurus Cabang Nahdlatul Ulama (PCNU) Pamekasan and associated autonomous bodies, have actively voiced peaceful religious narratives. These moderate narratives act as a counterbalance against the intolerant and exclusive religious ideas proclaimed by two aforementioned Islamist groups.